Legal Counseling as a Preventive and Responsive Effort Against Sexual Violence in Schools: A Community Service Program at SMP Negeri 20 South Tangerang - Aditya Maulana; Andika Adi Prasetyo; Chanda Alfira; Chika Antonia; Desva Ayu Anggraini; Hafsha Maulidya; Lidyanti Lidyanti; M. Adrian Kusuma; Shalsa Daniyanti (Abdimas Paspama, 2025)
Sexual violence in school environments has become an increasingly alarming issue, especially among junior high school students. Many victims, particularly female students, often remain silent due to fear and shame, which hinders efforts to provide protection and justice. This community service program aimed to raise awareness and educate students of SMP Negeri Dua Puluh South Tangerang on the prevention and handling of sexual harassment. Through legal counseling sessions, students were introduced to the concept of bodily autonomy, the importance of speaking up, and the legal protections available to them. The program applied a quantitative descriptive method, involving questionnaires, observations, and direct discussions to assess students’ understanding before and after the session. The findings suggest that legal education in schools can significantly enhance students’ ability to recognize, prevent, and report incidents of sexual violence. This initiative also highlighted the essential roles of schools, parents, and communities in safeguarding students' rights.